The Effects of Paternal Factors on Offspring Dental Eruption - McMillan, Luke (East Carolina University, 2017)
In a study conducted using rodents, it was found that a higher level of paternal physical activity prior to fertilization had a positive effect to decrease the offspring’s predisposition for metabolic syndrome. In another study conducted using human subjects, an examination of 145 offspring-parent groups showed significant positive correlation between paternal height and weight and offspring bone mineral density and content. While there is an established body of research examining maternal factors and their effects on offspring, such as tooth development, there has been very little examination of the influence of paternal factors on offspring health outcomes, such as tooth development. The objective of this study is to determine if there exists any correlation between paternal body mass index (BMI) and offspring tooth development. It is hypothesized that an increased paternal BMI will be associated with decreased offspring tooth development. To answer this question, we have recruited women and their children, 0-6 years of age, to participate in the study. All maternal participants completed a modifiable physical activity questionnaire, which acquired information about both parents: age, BMI, education level, and physical activity. All child participants were seen at the ECU pediatric dental clinic for standard dental screenings and clinic measures were collected directly. We classified parent:child pairs into 2 groups: group with paternal BMI 18.5-24.9 as Normal weight (NW) group, and group with paternal BMI >25 as Overweight or Obese (OW/OB) group. All women completed consent for themselves and their child. Mothers also completed a questionnaire, and the children received standard dental care. Alpha level was set a priori at 0.05 and multiple t-tests were performed to determine differences between groups and regression analyses were completed to look for significant associations. We recruited 23 parent-child pairs. There are no significant differences between paternal BMI groups with child tooth development. There are consistent trends of positive correlation between paternal normal weight BMI with child tooth development. Conversely, there is consistently negative correlation between paternal OW/OB (BMI) with child tooth development. These data suggest paternal BMI, an indicator of overall health of the father, is associated with child dental health. Further research is necessary to determine the extent of paternal health measures required to fully understand child tooth development and disease risk.
Keywords: BMI, Dental Development, Child, Offspring, Paternal